Identification of Candidate Chromosome Region Related to Melon (Cucumis melo L.) Fruit Surface Groove Trait Through Biparental Genetic Mapping and Genome-Wide Association Study - Du, Xin; Liu, Hongyu; Zhu, Zicheng; Liu, Shusen; Song, Zhengfeng; Xia, Lianqin; Zhao, Jingchao; Luan, Feishi; Liu, Shi (Frontiers in Plant Science, 2022)
The melon fruit surface groove (fsg) not only affects peel structure and causes stress-induced fruit cracking but also fits consumers’ requirements in different regions. In this study, genetic inheritance analysis of three F2 populations derived from six parental lines revealed that the fsg trait is controlled by a simple recessive inherited gene. Through bulked segregant analysis sequencing (BSA-seq), the Cmfsg locus was detected in an 8.96 Mb interval on chromosome 11 and then initially mapped to a region of approximately 1.15 Mb. Further fine mapping with a large F2 population including 1,200 plants narrowed this region to 207 kb containing eleven genes. A genome-wide association study (GWAS) with 187 melon accessions also produced the same chromosome region for the Cmfsg locus. Due to the rare molecular markers and lack of mutations in the coding and promoter regions of the 11 candidate genes in the fine-mapped interval, we conducted in silico BSA to explore the natural melon panel to predict candidate genes for the Cmfsg locus. A 1.07 kb segment upstream of MELO3C019694.2 (annotated as the AGAMOUS MADS-box transcription factor) exhibited a correlation with the grooved and non-grooved accessions among the F2 individuals, and a natural panel consisted of 17 melon accessions. The expression level of MELO3C019694.2 in the pericarp was higher in grooved lines than in non-grooved lines and was specifically expressed in fruit compared with other tissues (female flower, male flower, root, and leaf). This work provides fundamental information for further research on melon fsg trait formation and molecular markers for melon breeding.